Caroço de algodão em dietas para tilápia-do-Nilo: efeitos sobre a digestibilidade de nutrientes e histologia hepática e testicular - Lemes, Maysa Teodoro (2017)
The use of seed and cotton by-products in animal feed it has been highlighting positively in the field of nutrition, it being the cotton plant (Gossypiumspp) cultivated for fiber production, oil and how a by-product of the cotton, the bran has been outstanding worldwide as the second most important source or protein supplementation available for animal feed, just only it being surpassed by soybeans. Two experiments were carried out with aim of the verify the inclusion of cottonseed on nutrient digestibility and histology of the livers and testicles of tilapia. In the experiment of digestibility 144 juveniles were used with an average weight of tilapia 179.42 ± 23.45 g, distributed randomly in blocks design. Diets were elaborated for the purpose of contain different levels of inclusion of cottonseed (0; 1.5; 3.0 and 4.5%), offered five times a day at predetermined times. The apparent digestibility coefficients were determined using the indirect method using chromium oxide as inert marker (0.1%). The averages were subjected to analysis of variance (ANOVA). There was no variance between the blocks (p > 0.05). The ADCs of dry matter, crude protein, digestible protein, raw energy and digestible energy of diets were not influenced (p > 0.05). Cottonseed in diets containing levels of inclusion of up to 4.5% does not determine effects on utilization of nutrients and dietary energy supplied to the Nile tilapia. In the second experiment were used 320 broodstock with average weight of 316, 12 g, distributed in completely randomized design. Diets were elaborated in order to contain different levels of inclusion of cottonseed (0; 1.5; 3.0 and 4.5%), diets were offered twice a day at predetermined times. Histological changes of the livers were evaluated qualitatively using the index of BERNET, and testicular characterization was analyzed descriptively using standardized terminology to describe the reproductive development of fish, to the indexes gonadossomatic (GSI) and hepatossomatic (IHS) and visceral fat (VF) were submitted to analysis of variance (ANOVA) bifatorial. There was no difference (p > 0.05) between the analyzed indices and also no differences were found in histology of the testis, however it was observed on histology of liver, changes as the inclusion of cottonseed in diets. Cottonseed in diets containing levels of inclusion of up to 4.5% does not determine effects on spermatogenesis of broodstock of Nile tilapia.